Temporal and epidemiological evaluation of meningitis reports in the State of Paraíba, Brazil (Research, Society and Development, 2020)
The epidemiology of meningitis has worldwide distribution and its expression depends on different factors, such as the infectious agent, the existence of population clusters, socioeconomic characteristics of population groups and the environment. The present study aimed to analyze the cases of meningitis reported from 2008 to 2017 according to their evolution, etiology and age group affected in the state of Paraíba. Data were collected from the notification platform Sinan - Notification Disorders Information System. From the results obtained, it was observed that of the 822 cases reported in the ten years analyzed 14.82% resulted in death from the disease. It was observed that meningitis affects a varied age group of the population, being under 5 to 9 and adults from 20 to 39 years, the age group most affected by the disease. Additionally, children under 1 year to 4 years old presented relevant data, being an age group that should be considered in the epidemiological aspect.